PENGARUH KEPUTUSAN PENDANAAN, PROFITABILITAS DAN INVESTMENT OPPORTUNITY SET (IOS) TERHADAP RETURN SAHAM - B11111078, Eko Darmawan (Jurnal Manajemen Update, 2015)
The objective of this study was to investigate the influence of funding decision,profitability, and opportunity investment set on stock return. Population of thisstudy was public companies registered at Indonesia Stock Exchange with sampleof 16 manufacture companies in period of 2009 to 2013. Data of study wasanalyzed with double linear regression. The findings indicated that profitabilityhad significant and positive influence on stock return whereas funding decisionand funding decision and investment opportunity set demonstrated contradictoryoutcome.Keywords: Funding decision, profitability, investment opportunity set and stockreturn